Legal Analysis of the Criminal Act of Defamation Through Social Media - Putri Ramadhani rangkuty; Habiburriziq El Ardhy Saragih; Muhammad Fazli Pratama; Ahmad Yasin Dongoran; Raja Muda Pahlevi Siregar; Annisa Putri Andini Tanjung (ISNU Sumatera Utara, 2025)
The way society communicates has changed significantly as a result of advances in digital technology, particularly how ideas are expressed on social media. The rise in online defamation claims is one legal issue arising from the ease of access to information. The purpose of this essay is to examine the crime of defamation on social media from a legal perspective, using provisions from the Electronic Information and Transactions Law (UU ITE) and the Criminal Code (KUHP). Using a normative approach, it is found that the two legal instruments differ significantly in terms of the elements of the crime and their sanctions. Furthermore, it remains difficult for law enforcement to distinguish between insults and freedom of expression in defamation cases, particularly those related to criticism of public figures. To curb such violations, this essay also emphasizes the importance of restorative justice strategies and improving digital literacy. Thus, in the digital age, it is crucial to strike a balance between safeguarding freedom of speech and preserving individual dignity.